The protective role of selection, optimization and compensation in coping with self-control demands at work - Stefan Diestel; Klaus-Helmut Schmidt (ISM Research Journal, 2015)
In recent research, self-control demands have been found to predict high burnout and other forms of psychological strain. Self-control refers to a psychological mechanism, which enables people to override, inhibit or modify habits, spontaneous emotions or impulses and motivation-al tendencies, in order to regulate goal-directed behavior. In the present study, we tested mod-erating effects of coping strategies of selection, optimization and compensation (SOC-strategies) on the positive relationships between self-control demands and indicators of job strain. These strategies are conceptualized as individual mechanisms of building and conserving psychological resources. On the basis of a sample, which comprised 195 employees from a German financial institution, we found that the positive relationships of self-control demands to emotional ex-haustion, ego-depletion and depressive symptoms are attenuated as a function of selection, optimization and compensation. Our findings indicate that those three coping strategies pre-vent employees from being strained when their job role puts high demands on self-control. In particular, human resource management and organizational stress prevention strategies should focus on SOC-strategies as effective skills of developing resilience in facing high job demands.
Keywords: 650